Perceived Fitness Benefits and Competitive Engagement of Aero Gymnastics and Conventional Physical Education among Grade 7 - Jimenez, Zeela Mae; Ofrin, Darwin D. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
This study aimed to investigate the perceived fitness benefits and competitive engagement of aerobic gymnastics and conventional physical education (PE) exercises. A total of 90 students were selected through convenience sampling from the school where the research was conducted. The participants were randomly assigned to two equal groups: one group participated in an eight-week aerobic gymnastics program, while the other engaged in conventional PE exercises. A quasi-experimental non-equivalent control group design was utilized to achieve the study’s objectives, enabling a comparative analysis of the two interventions in a controlled environment. Data collection involved a teacher-made questionnaire based on a 4-point Likert scale, which comprised five statements under each subcategory to measure students' fitness levels and engagement. This tool provided a clear visual representation of the data. Participants engaged in distinct activity sets according to their assigned intervention: aerobic gymnastics or conventional PE exercises. For data analysis, both descriptive statistics (means and standard deviation) and inferential statistics (dependent and independent t-tests) were employed to assess changes within and between groups. The findings revealed that participation in both aerobic gymnastics and conventional PE exercises had resulted in significant improvements in students’ physical fitness and competitive engagement.